2020
DOI: 10.1111/ijd.14850
|View full text |Cite
|
Sign up to set email alerts
|

The role of integrins in melanoma: a review

Abstract: Integrins are the major family of cell adhesion receptors in humans and essential for a wide range of normal physiology, including formation and maintenance of tissue structure integrity, cell migration, proliferation, and differentiation. Integrins also play a prominent role in tumor growth and metastasis. Translational research has tried to define the contribution of integrins to the phenotypic aggressiveness of melanoma because such knowledge is clinically useful. For example, differential expression of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 78 publications
(100 reference statements)
1
20
0
Order By: Relevance
“…At present, IVL is mostly used as a marker protein to study skin keratinocyte differentiation (46,47). However, there are few reports of the associations between integrin and melanoma (48,49). In view of its important role in maintaining skin function, we can speculate that IVL may also play an important role in the progression of melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…At present, IVL is mostly used as a marker protein to study skin keratinocyte differentiation (46,47). However, there are few reports of the associations between integrin and melanoma (48,49). In view of its important role in maintaining skin function, we can speculate that IVL may also play an important role in the progression of melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported on the CP‐GEP model to identify patients with primary cutaneous melanoma who may forgo the sentinel lymph node (SLN) biopsy procedure because of their low risk of nodal metastasis 1,2 . The CP‐GEP model combines clinicopathologic (CP) variables, Breslow thickness, patient age, and the expression of eight genes related to epithelial‐to‐mesenchymal transition 3,4 to categorize patients into two groups: low risk or high risk for nodal metastasis (Fig. 1).…”
Section: Figurementioning
confidence: 99%
“…Eligibility was determined based on histopathology data derived from patient medical records and established by two or more board‐certified MC dermatopathologists. Patients were eligible for this study if they met criteria for an SLN biopsy by National Comprehensive Cancer Network guidelines 4 . Specifically, a patient was eligible if their melanoma was (i) tumor (T) stage 1a (Breslow thickness of less than 0.8 mm) with at least one of the following risk factors: ulceration, mitoses present, and patient age <40 years; or (ii) T1b to T3 melanoma (Breslow thickness of 0.8–4 mm).…”
Section: Figurementioning
confidence: 99%
“…Specifically, we have shown that the expression of integrin cell adhesion receptors is associated with the nodal metastasis of melanoma and may be quantified to identify patients in need of a sentinel lymph node biopsy (SLNb) 5 . Integrins are heterodimeric proteins composed of noncovalently linked ɑ and β subunits which are essential for a wide range of normal physiology and also play prominent roles in cancer 6 . The mammalian genome encodes for 18 ɑ and 8 β integrin subunits which combine to form 24 unique ɑ/β heterodimers 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The mammalian genome encodes for 18 ɑ and 8 β integrin subunits which combine to form 24 unique ɑ/β heterodimers 7 . When integrins bind to components of the extracellular matrix such as fibronectin, their cytoplasmic tail recruits and locally enriches a myriad of cell surface receptors, scaffolding proteins, and enzymes which stimulate fibrinolysis, angiogenesis, and tumor immune evasion 6 , 8 , 9 . Here we assembled a large cohort of patients diagnosed with primary cutaneous melanoma to identify integrin subunits associated with nodal metastasis.…”
Section: Introductionmentioning
confidence: 99%